Factors Influencing Agrarian Reform Policy Implementation: A Case Studi of Dairi Regency, Indonesia - Febrian Erikson Situmorang; Sutri Destemi Elsi; M. Wira Anshori; M. Yusuf (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study aims to analyze the factors influencing the implementation of agrarian reform policy in Dairi Regency, Indonesia, based on Presidential Regulation Number 62 of 2023. Agrarian reform is a strategic policy designed to address inequality in land ownership and improve community welfare. This research employs a qualitative approach with data collection techniques including in-depth interviews, observation, and documentation. The findings reveal that the implementation of agrarian reform in Dairi Regency has been carried out administratively, particularly through land certification programs as part of asset restructuring. However, the effectiveness of implementation is influenced by several factors, including limited human resources, budget constraints, and suboptimal coordination among implementing agencies. In addition, access reform and land dispute resolution have not been optimally implemented. These findings indicate that the success of agrarian reform policy is not only determined by policy design but also by institutional capacity and the broader context of implementation.